Outdoor Mathematics Learning Activities Based on Unplugged Coding Enhance Self-Regulated Learning: A Systematic Review - Anindya Nurista Usmut Anindya Nurista Usmut; Mohamad Aminudin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Technological advancements in the 21st century require the mastery of computational thinking from an early age. However, mathematics learning is often perceived as monotonous, leading to low levels of student self-regulation. This study aims to systematically review the effectiveness of developing outdoor mathematics activities based on unplugged coding in enhancing self-regulation. The method used was a Systematic Literature Review (SLR) following the PRISMA protocol, analyzing 35 research articles (2006–2026). The results indicate that unplugged coding activities are as effective as computer-based methods in training algorithmic logic. Outdoor learning has been shown to increase motivation and reduce boredom, while self-regulation strategies emerge as the primary predictor of success in solving mathematical problems. The study’s conclusion emphasizes that the integration of these three components—outdoor mathematics, unplugged coding, and Self-Regulated Learning—creates an interactive and self-directed learning environment that specifically contributes to enhancing students’ learning autonomy.